Psychiatric Commitment: Sixty Years Under the Scrutiny of the European Court of Human Rights - Niveau, Gérard; Jantzi, Camille; Godet, Tony (Frontiers in Psychiatry, 2021)
Background and Aims In the field of mental health, the fundamental right to liberty is a point of tension between the practice of psychiatric commitment on the one hand and the universal concept of human rights on the other. The European Court of Human Rights (ECHR) is a very specific means of safeguarding human rights because it allows an individual to not only assert their rights but also compel a state to bring its legislation into conformity with the principles of the European Convention on Human Rights. The aim of this study was to gather the case-law of the ECHR on psychiatric commitment over the last 60 years and to determine how this case-law has affected national legislation and therefore psychiatric practice. Methods Jurisprudence data were collected from the HUDOC ECHR database, and the direct effects of the ECHR judgements on the legislations of the countries concerned were collected from the HUDOC EXEC database of the Council of Europe. The case-law of the Court included 118 judgements and 56 decisions and concerned 31 of the 45 countries that have ratified the Convention. Results This study therefore showed a direct effect of the Court's case-law on the legislation on psychiatric commitment in the various countries that have ratified the Convention. It was also possible to detect an indirect effect of this case-law through the directives of international institutions such as the directives of the Committee of Ministers of the Council of Europe concerning respect for people with mental disorders. Conclusions The ECHR case-law therefore has a major influence on the psychiatric practice in all Council of Europe countries.